Education policies for Special Education in Brazil: a brief historical background (Práxis Educativa, 2010)
The present paper delivers an analysis and a systematization of the Brazilian legislation (from the nineteenth century to the year 2009) regarding the education of disabled people, as well as their rights and the services meant to support them. This research, which is based on collected data from relevant literature and documents, reviews the historical process of the trajectory of the Special Education in Brazil. The study indicates that educational policies in Brazil have identified the Special Education students differently over time. The teaching of students with disabilities or who failed to adapt themselves to regular education was offered separately from the common education. Due to the advancements on studies and research in the fields of Education and Human Rights, educational laws and practices began to change, which prompted the need of a reorganization of both the common schools and the special schools. Keywords: Special Education. Educational Inclusion. Education Policy.